Get a vocation: keeping on top of studies : reducing the drop-out rate in vocational upper secondary education and training - Jäppinen, Aini-Kristiina [Verfasser] (My University, 2009)
"The Finnish Ministry of Education commissioned a study in 2006-07 on reducing the number of drop-outs, 'Get a vocation - keeping on top of studies'. The aim of the study was to establish the good practices and operating models underpinning reduction in drop-outs. The study indicates that an educational institution that fosters commitment of students to their studies acts systematically and persistently when facing challenges. It examines its operations critically. It creates a safe and caring learning environment in which certain basic principles prevail, but it is nevertheless flexible. In such educational institutions, pedagogically distributed leadership manifests itself in five key areas: management support groups, the general effectiveness of work on the curriculum, the practices of strategic plans and development work, on-the-job learning, and the multiprofessional nature of educational guidance." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); P 2.1.1 Ohne Schulabschluss; S 5.1 Bildungsmanagement; L 1.3 Curriculumentwicklung; I 2.2.1 Westeuropa; Ausbildungsabbruch; Schulabbrecher; Bildungsmanagement; Curriculumentwicklung; Berufsorientierung; Finnland